Investigating the Impact of Augmented Reality (AR) as an Interactive Tool in Teaching English Vocabulary: A Literature Review - Tira Nur Fitria (International Journal of Computer and Information System (IJCIS), 2026)
This research investigates the impact of Augmented Reality (AR) as an interactive tool in teaching English vocabulary. This study employed a literature review design to investigate the impact of AR as an interactive tool in teaching English vocabulary. Research on AR in vocabulary learning has consistently demonstrated its positive impact on students' motivation, retention, and learning outcomes. Key findings from 28 studies highlight several advantages of AR in vocabulary instruction. Studies on AR in vocabulary learning have consistently shown its positive influence on students’ motivation, retention, and learning outcomes. AR has been proven to significantly improve vocabulary retention, enabling students to remember words for longer periods compared to traditional methods such as flashcards or lecture-based approaches. It also creates a more engaging and interactive environment, which increases students’ enthusiasm and motivation to learn vocabulary. Research further indicates that AR is effective across different age groups, from preschool to high school, supporting both low-achieving and advanced learners. Many studies highlight that students using AR perform better in vocabulary tests than those using conventional learning strategies. Comparisons between AR and tools like flashcards or multimedia suggest that AR is more engaging, interactive, and effective in enhancing vocabulary mastery. However, several challenges exist in implementing AR, including limited access to technology, a lack of teacher training, and the relatively high cost of AR devices and applications. The success of AR-based learning also depends on the support of parents and teachers, as parental involvement and teacher readiness play a vital role in ensuring its effective integration into the classroom. Overall, AR holds great potential as an innovative tool to enhance vocabulary learning, provided that the technological, financial, and pedagogical challenges are addressed.